Determination of chemical structure of antioxidant compound benzophenon glycoside from n-butanol extract of the fruits of Mahkota Dewa [Phaleria macrocarpa (Scheff) Boerl.] - Risma Marisi Tambunan; Partomuan Simanjuntak (Indonesian Journal of Pharmacy, 2006)
In continuing of chemical study research on the parts of the fruits of Mahkota dewa, we have done isolated one antioxidant compound benzophenon glycoside from n-butanol extract. Isolation and purification by column chromatography (SiO2, chloroform-methanol) and determination of chemical structure based on interpretation spectra of ultraviolet (UV), infrared (IR) and nuclear magnetic resonance 1 dimension (1H & 13C NMR), 2 dimension (1H-1H COSY, 13C-1H COSY, HMBC). Based on spectrroscopic data, the compound was identified as 6,4’,-dihidroksi-4- metoksibenzofenon-2-O-α-D glucopyranoside.Key words: Mahkota dewa, Phaleria macrocarpa, Thymelaceae, Indonesian medicinal plant, benzophenone glycoside